Resolusi Konflik dalam Institusi Pendidikan Islam (Kajian Empirik dan Potensi Riset Resolusi Konflik) - Khafidz Fuad Raya , Moch. (Jurnal Pendidikan Islam Indonesia, 2016)
Humans as social beings will not escape with a name conflict. Conflict is an essential part of organizational life, conflict is a vehicle for the coloring of life, without any conflict meaningless life. Conflict can cause negative effects for the organization of Islamic education, but conflict can also have a positive impact for the survival of the organization's performance. Through conflict, communication is woven possessed frequency better if conflicts are managed properly, and used as an opportunity to make a change. On the other hand, the conflict if not managed properly, it will have an impact on the resistance of communication within the organization. Management adapted to the anatomy and diagnosis of conflicts that have arisen, so that the diagnosis of conflict can be detected as early as possible so that the conflict is not as a negative impact, but conflict can be used as an opportunity to make a breakthrough in the development of organizational performance.